A fast evaluation of initial configurations in repeatable inverse kinematics for redundant manipulators - Dulęba, Ignacy; Karcz-Dulęba, Iwona; Mielczarek, Arkadiusz (Zielona Góra: Uniwersytet Zielonogórski)
A repeatable inverse kinematic task in robot manipulators consists in finding a loop (cyclic trajectory) in a configuration space, which corresponds to a given loop in a task space. In the robotic literature, an entry configuration to the trajectory is fixed and given by a user. In this paper the assumption is released and a new, indirect method is introduced to find entry configurations generating short trajectories. The method avoids a computationally expensive evaluation of (infinite) many entry configurations for redundant manipulators (for each of them, repeatable inverse kinematics should be run).
Keywords: manipulator; repeatable inverse kinematics; initial configuration; optimization